2023
DOI: 10.47197/retos.v50.99573
|View full text |Cite
|
Sign up to set email alerts
|

Short Term HIIT increase VO2max, but can’t decrease Free Fatty Acids in Women Sedentary Lifestyle

Fajar Syamsudin,
Lilik Herawati,
Ema Qurnianingsih
et al.

Abstract: Previous studies have investigated the effects of high-intensity interval training (HIIT) on cardiorespiratory fitness and body composition in overweight populations. However, short-term effect of HIIT and free fatty acids (FFA) serum in women sedentary lifestyle is not clearly understood. The aim of this study was to investigate the effect of 2-week high intensity interval training on body fat percentage, free fatty acids, and VO2max in overweight sedentary adult women. The fourteen sedentary young women (18–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Lastly, monitoring subjects becomes more convenient as they can remain stationary without switching locations or equipment during training (Hoeger et al, 2019). In the data analysis phase, findings from seven studies (Allen et al, 2017;Gillen et al, 2016;Kong et al, 2016;Polytechnic Institute of Beja (Portugal), 2023;Reljic et al, 2020;Syamsudin et al, 2023;Vella et al, 2017) revealed that research participants exhibited VO2max values as moderate both before and after the intervention period. Additionally, three studies (Astorino et al, 2013;Reljic et al, 2018;Vigriawan et al, 2022) documented an enhancement in VO2max levels from low to moderate subsequent to the prescribed training program.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lastly, monitoring subjects becomes more convenient as they can remain stationary without switching locations or equipment during training (Hoeger et al, 2019). In the data analysis phase, findings from seven studies (Allen et al, 2017;Gillen et al, 2016;Kong et al, 2016;Polytechnic Institute of Beja (Portugal), 2023;Reljic et al, 2020;Syamsudin et al, 2023;Vella et al, 2017) revealed that research participants exhibited VO2max values as moderate both before and after the intervention period. Additionally, three studies (Astorino et al, 2013;Reljic et al, 2018;Vigriawan et al, 2022) documented an enhancement in VO2max levels from low to moderate subsequent to the prescribed training program.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it increased fitness levels by up to 17%. Decreased HR rest after regularly doing HIIT is possible due to the induction of improved stroke volume (Syamsudin et al, 2023). Enhancement of stroke volume will increase plasma volume, thereby increasing myocardial contractility, which will lead to a decrease in HR rest (Vigriawan et al, 2022).…”
Section: Hiit Effectively Improves Physical Fitnessmentioning
confidence: 99%
See 2 more Smart Citations